2022
DOI: 10.3390/jcm11195949
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Block Decreases Chronic Postoperative Pain Severity in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Up to 56% of patients develop chronic postsurgical pain (CPSP) after coronary artery bypass grafting (CABG). CPSP can affect patients’ moods and decrease daily activities. The primary aim of this study was to investigate CPSP severity in patients following off-pump (OP) CABG using the Neuropathic Pain Symptom Inventory (NPSI). This was a prospective cohort study conducted in a cardiac surgery department of a teaching hospital. Patients undergoing OP-CABG were enrolled in an erector spinae plane block (ESPB) gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…186 Preventative perioperative use of ESPB was found to reduce the incidence and severity of persistent postoperative pain after off-pump CABG surgery (category B1-B evidence). 187 Continuous ESPB-related analgesia with LA alone 188 or when combined with dexamethasone 189 or dexmedetomidine 190 was found to be comparable to epidural 188 (for the first 12 hours) as well as superior to patient-controlled analgesia 189 and intravenous dexmedetomidine 190 with regard to pain scores 188,190 and opioid consumption 189 after cardiac surgery (category A2-B evidence 189,190 /category A3-E evidence 188 ).…”
Section: Fascial Plane Blocksmentioning
confidence: 91%
See 1 more Smart Citation
“…186 Preventative perioperative use of ESPB was found to reduce the incidence and severity of persistent postoperative pain after off-pump CABG surgery (category B1-B evidence). 187 Continuous ESPB-related analgesia with LA alone 188 or when combined with dexamethasone 189 or dexmedetomidine 190 was found to be comparable to epidural 188 (for the first 12 hours) as well as superior to patient-controlled analgesia 189 and intravenous dexmedetomidine 190 with regard to pain scores 188,190 and opioid consumption 189 after cardiac surgery (category A2-B evidence 189,190 /category A3-E evidence 188 ).…”
Section: Fascial Plane Blocksmentioning
confidence: 91%
“…186 Preventative perioperative use of ESPB was found to reduce the incidence and severity of persistent postoperative pain after off-pump CABG surgery (category B1-B evidence). 187…”
Section: Regional Techniquesmentioning
confidence: 99%
“…Both studies showed that ESPB was effective. However, one study was retrospective [24], and the other was an observational study [25]. The current trial is a high-quality RCT; therefore, it provides primary evidence that performing ESPB in OPCAB patients may be a safe analgesic option for the primary care physician.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…However, there are only a limited number of RCTs [23]. To the best of the authors' knowledge, there are two studies evaluating the effectiveness of ESPB in patients undergoing OPCAB [24,25]. Both studies showed that ESPB was effective.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In a clinical study of extremity amputation, the prolonged use of peripheral nerve block catheters considerably reduced the incidence and severity of phantom limb pain [73]. Recently, several ultrasound-guided interfascial plane blocks have shown promising results in preventing CPSP [74][75][76]. However, the precise effects of these blocks on CPSP remain difficult to determine.…”
Section: ) Regional Analgesiamentioning
confidence: 99%